Language Craft by Nigerian and Ghanaian Christian Preachers-What Impact? (Global Journal of Human-Social Science, 2015)
The increasing language craft by Pentecostal pastors is the focus of this study. The study area is communication language in the sermon of Christian preachers. Quantitative and qualitative survey methods were used. The communication goal of the preachers was investigated alongside the effectiveness of the use of the style as a means of communicating the pastors' message. The audience's perception of pastors who use the style and the effect of the style on them were also investigated. Study findings show that pastors use the style to facilitate attention and retention on the part of the congregants, a large percentage of the respondents hold pastors who adopt the style in high esteem and the style is also effective from the perspective of the respondents who are Pentecostal church members. It is recommended that pastors avoid over-generalisation in using this style.
Keywords: language craft; pentecostal preachers; communication goal; congregant2019; s perception; communication effectiveness